Sequence and Chronology of the Eruption of the Permanent Canines and Premolars in Romanian Children - Feraru Ion-Victor; Raducanu A.M; Feraru S.E; Herteliu C. (Romanian Society of Oral Rehabilitation, 2011)
Introduction. Teeth eruption is a dynamic, genetically dictated process which is a part of the odontogenesis and comprises all of the tooth's movement from the bone crypt where it formed until reaching the occlusal plane and starting its function. Chronologically normal eruption is defined as the situation in which dental eruption takes place at time moments placed around the medium eruption age calculated on large population samples. Aims. Determining the medium eruption age of the teeth emerging in the second stage of the permanent teeth eruption (canines and premolars) in children from Bucharest, Romania. Material and method. The retrospective transversal study was conducted on a sample of 2081 Caucasian children aged between 8 and 13 years who presented to the Paedodontics Clinic for consultation and treatment in the period 2006-2011. The statistical analysis used specific descriptive and interferential (confidence intervals) methods. Results. The permanent canines and premolars erupt in the age interval between 9 years 6 months and 11 years and 6 months in the following sequence: first upper premolar, lower canine and first premolar, second upper premolar, second lower premolar, upper canine. The study revealed the existence of differences in the sequence and timing of the eruption according to gender and dental arch. The maxillary eruption occurred earlier in girls than in boys and the situation in the mandible was similar except for the first premolar which erupted earlier in boys. Discussions and Conclusions. Overall the results of the study are in accordance with data from many studies previously performed, with a few differences in what concerns the sequence of eruption of upper canines and premolars in girls.